CHEMICAL CONTROL OF SUNFLOWER DOWNY MILDEW CAUSED BY PLASMOPARA HALSTEDII - H. B. PHAD, M. A. PATIL, M. S. RAMTIRTHKAR AND (Indian Phytopathology, 2002)
The 'efficacy of seven fungicides was tested against downy mildew of sunflower. Metalaxyl (Apron 35 SO) at 6 g/kg seed reduced the downy mildew incidence. Rhoda was an effective fungicide in reducing the disease but it was at par wuh fosetyl-Al while thiophanate methyl and carbendazin were ineffective. Phytoalexin GÂ·84 was effective when sprayed on the radicle of germinated seeds after inoculation.